2D axisymmetric transient inverse heat conduction analysis of air jet impinging on stainless steel plate with finite thickness. (25th January 2016) - Dou, Ruifeng; Wen, Zhi; Zhou, Gang
Highlights: A 2D axisymmetric inverse transient heat-conduction model was build. Equivalent Nusselt numbers of air jet impinging on metal plate were obtained. Equivalent Nusselt numbers reach peak values shortly after air jet start. Equivalent Nusselt numbers remain almost constant after the peak points. Abstract: A 2D axisymmetric inverse heat-conduction model based on the Levenber–Marquardt method was built. The equivalent Nusselt number Nuequ of air jet impinging on a stainless steel plate with finite thickness were obtained. Radiant heat transfer is significant when the temperature of the target plate is high, which induces the nonlinear feature of the inverse heat-conduction problem. The results of the experiments and the inverse analysis provide the following findings. First, the inverse heat-conduction model is accurate. Second, Nuequ maintains a relatively small value before the onset of the air jet. After the air jet starts, however, the values of Nuequ within the stagnation zone (dimensionless radius R / D n  ≤ 1.0) increase dramatically, reach the peak points in the next 20 s, and then remain nearly constant until the end of the experiments. Third, the radial distribution of Nuequ shows that it decreases rapidly within the region of R / D n  ≤ 8.0. When R / D n exceeds 10, Nuequ appears unaffected by the Reynolds number and R / D n . Lastly, Nuequ decreases slowly with the increase in time, which indicates that radiant heat-transfer flux decreases with target plate temperature.